State Amends for Lawful Harm Doing - Colleen Murphy; Jennifer K. Robbennolt; Lesley Wexler (Oñati Socio-Legal Series)
This essay explores the justifications for offering amends to victims of lawfully caused harm and the nature of amends in such contexts. In particular, we examine instances in which a state actor commits a grave, but lawful, harm to another, exploring why and how the state ought to respond to victims of lawful harm. This aspect of harm doing is often overlooked, but directly addressing the lawful harm that states cause is a vital part of an appropriate state response to having caused grave, though lawful, harm. First, we explore some general reasons why making amends is a morally appropriate response to lawful harm doing. Second, having justified why states ought to respond to the lawful harm they create, we move to outline a set of appropriate responses. These responses are grounded in the empirical literature on amends and apology and satisfy a number of the moral reasons it may be appropriate for states to offer amends. We offer some specific suggestions for managing amends in the military and police settings, though the basic elements of our proposal might also help inform response to the wider spectrum of lawful harms imposed by the state.